Organizational Restructuring and Performance of Business Organizations. The Case of Uganda Christian University - Caroline Kahunde (Uganda Christian University, 2025)
The study examined the effect of organizational restructuring on performance of business organizations: a case of Uganda Christian University (UCU). It specifically focused on; examining the effect of structural changes on the performance of business organizations, examining the effect of workforce adjustment on the performance of business organizations, and examining the effect of process reengineering on the performance of business organizations. The study was carried out using a cross-sectional study design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews and during data collection; both simple random and purposive sampling methods were used. A sample size of 44 respondents who are lower-level employees from the administration department of UCU and the top management in UCU was also used in the study. The study findings revealed that organizational restructuring at Uganda Christian University—through structural changes, workforce adjustment, and process reengineering—significantly enhanced institutional performance. Structural changes improved communication, decision- making, and efficiency, showing a strong positive correlation (r = .582**, p < .05) and a significant predictive value (β = 0.297, t = 2.601, p = 0.013). Workforce adjustment improved productivity and adaptability, also exhibiting a strong correlation (r = .591**, p < .05) and significant influence on performance (β = 0.204, t = 1.655, p = 0.016). Process reengineering, which streamlined workflows and boosted innovation, had the strongest impact with the highest correlation (r = .692**, p < .05) and regression significance (β = 0.465, t = 3.943, p = 0.000), confirming its critical role in driving organizational success. Finally, the study recommended the need for Uganda Christian University prioritize continuous process reengineering, adopt new technologies, enhance employee involvement in restructuring, focus more on process redesign over structural adjustments, and implement a strategic restructuring plan to sustainably improve organizational performance and efficiency
Undergraduate